Sedimentary logs and facies characterization dataset of Tembeling Group from the vicinity area of Kuala Tahan, Pahang, Malaysia. - Wei Chung Khor; Kamal Roslam Mohamed; Mohamed Shafeea Leman; Che Aziz Ali (Elsevier, 2023)
This sedimentary logging and facies characterized dataset of 28 outcrops exposed along Kuala Tahan – Kampung Pagi – Kampung Bantal which is situated in the central part of Peninsular Malaysia (in the state of Pahang). This dataset is recorded in 2017 during the construction of roadway. It consist of Mangking Formation of Tembeling Group with the total length of 410 m. The outcrops are arranged into 8 continuous sections. This data can be further correlated stratigraphically to produce composite log, facies analysis, depositional processes, and the depositional environment.